Prime Minister’s Decree No. 506 for the Year 2015 Amended by the Rectification Published in the Official Journal, Issue No. 13, Dated 26/3/2015 = قرار رئيس مجلس الوزراء رقم 506 لسنة 2015 معدل بالاستدراك المنشور بالجريدة الرسمية - العدد 13 فى 26/3/2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic